Main risk factors associated with pressure injury in the calcaneal region: a systematic review (Research, Society and Development, 2022)
Objective: To analyze the main risk factors associated with pressure injuries in the calcaneal region. Methodology: This is a systematic review carried out using the PRISMA method, in the electronic databases PubMed, Scopus and Web of Science, using the following descriptors: “Pressure Ulcers”, “Bedsores”, “Decubitus Ulcers”, “Heel”, “Calcaneus”, “Risk Factors” and “Contributory Factors”. Full texts, available in Portuguese, English or Spanish, published between January 2016 and May 2022 were included. In addition to these criteria, studies with participants aged 18 years and over and that investigated risk factors for the development of pressure injury in the calcaneus region regardless of stage level (I-IV), including non-classifiable injuries. Results: 05 articles made up the final sample of this study, with the highest production on the European continent (n: 03). Nine categories of risk factors associated with the development of pressure injuries in the calcaneal region were identified, ranging from the advanced age of patients to clinical characteristics such as diabetes mellitus and vascular disease and the presence of moisture, incontinence, friction and shear. Conclusion: Despite the scarcity of studies on risk factors for pressure injuries in the calcaneal region, there were several conditions that can increase the probability of occurrence of these injuries. However, more research is needed to elucidate these risk factors, in addition to well-designed studies to add to the body of evidence.